How to stop a hijacking : critical thinking in civil aviation security - Biles, Clay W. (Boca Raton : CRC Press, 2023)
Hijackings and bombings have plagued civil aviation since 1930 and air rage incidents are on the rise. While there is aircraft and inflight training available for air marshals, other first responders receive minimal training on inflight security awareness and protocols. There are no other resources currently available to flight crews or armed first responders that specifically address inflight security and how to address threats of disturbances on airplanes. How to Stop a Hijacking provides readers with fundamental principles on how to think more critically about onboard security threats. The aircraft cabin poses unique environment and security challenges, and first responders can apply security awareness and critical thinking skills to establish a safer environment in the cabin and airport for everyone onboard. The lessons in this book are driven with the central objective of teaching the reader how to counter inflight aggression and maintain tactical control of the cabin. Written by a former federal air marshal instructor, this book looks at the recent rash of air rage incidents and violence on airplanes, in addition to the real and ever-present threat of hijack or potential explosive device. How to Stop a Hijacking is a practical guide that offers methodological and tactically proven strategies for stopping violent acts onboard an aircraft inflight.
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Hijacking of aircraft -- Prevention; TRANSPORTATION / Aviation / General; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; POLITICAL SCIENCE / Political Freedom & Security / Intelligence